2018
DOI: 10.4218/etrij.2017-0082
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Intention to Protect Personal Information among Facebook Users

Abstract: This study aimed to examine predictors of the intention to protect personal information on Facebook. We conducted an online survey of 679 Facebook users in the Republic of Korea. The findings of this study showed that usefulness and ease of use had significant effects on attitudes toward protection behavior. The results also revealed that risk factors (privacy risk severity and vulnerability) had significant effects on protective behaviors. Based on our findings, we discussed the information protection of priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Second, understanding the role of individuals' beliefs can be served through the lenses of TAM while explaining the role of security concerns in affecting students' decisions to adopt smartwatches can be achieved through the perspective of PMT. Third, while the integration of these two models has already been validated in the previous literature (Chon et al, 2018;Alexandrou and Chen, 2019), it is believed that smartwatches have distinct features (Ogbanufe and Gerhart, 2018), and it is expected that the factors affecting the students' adoption of these wearables would also be different. Smartwatches are characterized by several features, such as non-visual aesthetics, high-pitched voices and touch-sensitive screens (B€ olen, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Second, understanding the role of individuals' beliefs can be served through the lenses of TAM while explaining the role of security concerns in affecting students' decisions to adopt smartwatches can be achieved through the perspective of PMT. Third, while the integration of these two models has already been validated in the previous literature (Chon et al, 2018;Alexandrou and Chen, 2019), it is believed that smartwatches have distinct features (Ogbanufe and Gerhart, 2018), and it is expected that the factors affecting the students' adoption of these wearables would also be different. Smartwatches are characterized by several features, such as non-visual aesthetics, high-pitched voices and touch-sensitive screens (B€ olen, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Theory integration research not only studies the relationship between independent variables and dependent variables, but also discusses the relationship between independent variables. For example, B.S.Chon et al integrated theory of planned behavior, protection motivation theory and technology acceptance model, studied SNS user privacy protection intentions, and found that the usefulness and ease of use in the technology acceptance model had a positive impact on the privacy protection attitude in the theory of planned behavior [25].…”
Section: Theory Application Methodsmentioning
confidence: 99%
“…The theories used in the research on SNS user privacy protection behavior at home and abroad mainly include communication privacy management theory [9], theory of planned behavior [7,14,17,24,25], protection motivation theory [13,18,25], uses and gratifications theory [13], fear appeal theory [4], social capital theory [6], social role theory [6], social cognition theory [26]. The models used include technology acceptance models [17,25].…”
Section: Main Theories and Modelsmentioning
confidence: 99%
See 2 more Smart Citations